Utilization of Bio-Mos® Mannan Oligosaccharide and Bioplex® Copper in Broiler Diets - Waldroup, P.W.; Fritts, C.A.; Yan, Fenglan (International Journal of Poultry Science, 2002)
A study was conducted to evaluate the effects of combinations of antibiotics, mannan oligosaccharides, and organic forms of copper in the diet of broilers. Male broilers in litter floor pens were fed nutritionally complete diets with a 2 x 2 x 3 arrangement of treatments including two antibiotic programs (none; 55 mg/kg bacitracin methylene disalicylate from 0 to 42 d followed by 16.5 mg/kg virginiamycin to 63 d), two levels of mannan oligosaccharide (none; 1 g/kg Bio-Mos® from 0 to 42 d followed by 0.75 g/kg to 63 d) and three copper programs (none; copper sulfate to provide 250 mg/kg from 0 to 42 d followed by 62.5 mg/kg to 63 d; Bioplex® Cu to provide 55 mg/kg from 0 to 42 d followed by 27.5 mg/kg to 63 d). This resulted in a total of 12 experimental treatments, each fed to eight pens of 50 male chicks. Birds and feed were weighed at intervals during the study and samples of birds processed at 63 d to determine dressing percentage and parts yield. Body weight and feed conversion at 21 d was significantly improved by addition of the antibiotics but did not prove to be significantly improved at later ages. Addition of copper from either copper sulfate or Bioplex® Cu had no significant effect on any parameter tested. Addition of Bio-Mos® at the levels tested had no significant effect on any parameter but did interact with some of the other factors. Carcass characteristics were not improved by any of the factors tested. It is possible that the level of Bio-Mos® used in this study was not sufficient to elicit a positive response.